Técnicas de computação afetiva aplicadas a testes psicológicos computadorizados - Inácio, Deusdete Vieira (2023)
The present work presents contributions in the evaluation of aspects related to the applicability of affective computing techniques to computerized psychological tests, describes the implementation of a prototype of an expert system of computerized psychological testing, built under a specific systemic architecture, pointing out the real contributions in the transformation from office protocols (pen, paper and observation) to computerized versions more sensitive to the patient's emotional states. In this way, the basic concepts that guided the development of the work are presented, as well as the current state of the art in this scenario. A specific system architecture is proposed for this context, with emphasis on the adoption of an affective computing module and, through tests and evaluations by specialist psychologists, it demonstrates the obtained results that support its viability.